Molecular interaction studies in binary liquid mixture through ultrasonic measurements at 303.15k - Santhi, N.; Madhumitha, J. (International Journal of Advanced Chemistry, 2014)
The ultrasonic velocity (U), density (?) and viscosity (?) have been measured for the binary liquid mixtures containing 2-(p-methoxy phenylsulphonyl)-4-methyl sydnone in Ethanol at 303.15K. From these data some of acoustical parameters such as adiabatic compressibility (?), free length (Lf), acoustic impedance (Z), relative association (RA), relaxation strength (r), Rao’s constant (R), molar compressibility (W), relaxation time (?), Vander waal’s constant (b), free volume (Vf)  and internal pressure (?i) have been computed using the standard relations. The results have been discussed in terms of molecular interactions.   Keywords: Binary mixture, Molecular interaction, ultrasonic velocity, density, viscosity.